A Phenomenological Investigation of Trauma in 18 Adults Living With Inflammatory Bowel Disease. (January 2023) - Glynn, Heidi; Knowles, Simon R.
While trauma is recognized as being common in Inflammatory Bowel Disease (IBD) cohorts, limited research has explored how trauma impacts the lived experience of IBD. The aim of this study was to develop an understanding of how trauma impacts the experience of living with IBD and its subsequent management. An interpretative phenomenological analysis with thematic analysis was conducted. Eighteen adults with IBD participated in this qualitative research study. Key themes identified included: (1) Trauma was associated with the journey of IBD; (2) the impact of IBD and trauma, and (3) coping strategies. Pre-existing non-IBD trauma was prevalent, with several participants reporting links between traumatic events and their IBD diagnosis. Experiences of IBD trauma were described by participants across all stages of their illness journey. The study can assist healthcare professionals to better understand the experience of living with IBD and trauma and the factors that can contribute to traumatic responses.